What are you looking at? the surprising, shocking, and sometimes strange story of 150 years of modern art - Gompertz, Will 1965- (Dutton, 2012)
"We all know what Modern Art looks like. We've seen Monet's water lilies, we've admired Picasso's nudes, and we've gawked at Damien's shark, as well as the price tag. But what does it all mean? What is Modern Art? Who started it? Why do we love/hate it? And why is it such big money? What Are You Looking At? takes the reader on a captivating tour of modern art from Impressionism to the present day, telling the story of the movements, the artists and the wonderful works that not only changed art forever, but helped create and define the modern world. Refreshing, irreverent and extremely accessible, the book is rich with extraordinary tales and anecdotes - a coffee morning in Paris with Monet and the Impressionists, Marcel Duchamp purchasing his famous urinal, Sir Nicholas Serota, the Director of the Tate Empire confessing his terror at not knowing what to think every time he encounters a work of art for the first time. It also lifts the lid on the astronomically expensive art sales - how buying modern art has become a sound investment- and explains how the market really works - the artists, the dealers, the auction houses and the curators. With wonderful humor, down-to-earth storytelling, and a flair for odd details that spark insights, Will Gompertz is the perfect tour guide for Modern Art. He is a former director of the Tate Gallery in London and the BBC Arts Editor, so he brings both considerable expertise and genuine love of the subject to this informative and engaging narrative. What Are You Looking At? doesn't just tell you if a work of art is any good or not; it does much better than that. Will Gompertz arms us with the knowledge to be in a position to make our own minds up by telling us the one thing that we've always wanted to know: what are we looking at?"-- Provided by publisher.